The Relationship Between Family Support And The Quality Of Life Of Patients With Chronic Renal Failure Who Are Undergoing Hemodialysis - Piddy Lhoksuma Erlyana Naceda; R.A Gabby Novikadarti Rahmah; Faisal Kholid Fahdi; Suhaimi Fauzan; Muhammad Luthfi (Critical Medical and Surgical Nursing Journal, 2026)
Introduction: family support can affect the quality of life of hemodialysis patients. With family support in providing motivation, CKD patients undergoing hemodialysis have a stimulus to improve their quality of life. This study aims to analyze the relationship between family support and the quality of life of chronic kidney failure patients undergoing hemodialysis at Hospital in Pontianak.   Methods: This study is quantitative in nature, using a correlational design with a cross-sectional approach. The sample was taken using the total sampling technique with a total of 74 respondents. Data collection was conducted using the Family Support and Quality of Life questionnaire. (KDQOL-SF TM 1.3). Statistical tests used the Spearman rank correlation test.   Results: The univariate analysis showed that most respondents were aged 46-65 years (56.8%) and were female (52.7%). Almost all respondents were married (90.5%) and had a high school education (40.5%), with the fewest respondents having a college education, totaling 12 people (16.2%), and the majority being unemployed (62.2%). Most respondents had good family support and a moderate quality of life (52.7%). The result of the Spearman correlation test between family support and quality of life among hemodialysis patients showed a correlation coefficient of rho = −0.016 with a p-value of 0.839 (p > 0.05). This finding indicates a very weak negative correlation and statistically non-significant relationship between family support and patients’ quality of life. Therefore, family support was not significantly associated with the quality of life of hemodialysis patients in this study.   Conclusion: In this study, it can be concluded that there is no relationship between family support and the quality of life of chronic kidney failure patients undergoing hemodialysis at RSU Yarsi Pontianak.